Effort-reward imbalance and heavy alcohol consumption among humanitarian aid workers - Jachens, Liza; Houdmont, Jonathan; Thomas, Roslyn (Alcohol Research Documentation, 2016)
Objective: The purpose of the study was to explore the prevalence of heavy alcohol consumption and its association with stress-related working conditions - defined in terms of effort-reward imbalance (ERI) - among a large sample of humanitarian aid workers (HAWs) operating across four continents. Research has shown employee alcohol consumption has potential detrimental implications for health and work outcomes and is associated with exposure to work stressors. Research to identify links between stressful aspects of work and heavy alcohol consumption among HAWs could usefully inform the design of sector-specific interventions concerned with the reduction of alcohol consumption. Method: Questionnaire data were obtained from 1063 women and 917 men working in an international humanitarian agency. Logistic regression analyses were conducted separately for men and women (with different cutoff points to identify heavy drinking) to investigate the relationship between ERI and the risk of heavy alcohol consumption while controlling for a host of socio-demographic and occupational variables. Results: The prevalence of heavy alcohol consumption among women (18%) was higher than the corresponding rate for men (10%). Results lent support for the effort-reward perspective among women only: intermediate and high ERI in females was associated with a tripling of risk for heavy alcohol consumption. Conclusions: Interventions to reduce effort-reward imbalance among female HAWs might help to reduce heavy drinking within this population.